ASSESSMENT OF THE PREVALENCE OF CONGENITAL HEART DEFECTS PER PREGNANT WOMAN MANAGING PREGNANCY AT THE PRENATAL AND NEONATAL DIAGNOSTIC SCREENING CENTER IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objectives: Assessment of the prevalence of congenital heart defects per pregnant women forpregnancy examination and management at the prenatal and neonatal diagnostic screening centerin 2021.Subjects-methods: From 1/2021 to 12/2021, 2159 pregnant women came to fetalmorphological ultrasound at the prenatal and neonatal screening center of Nghe An Children'sHospital, a retrospective cross-sectional descriptive research method.Results: There were 760 cases of fetal morphological abnormalities, accounting for 35.2%. In760 abnormal cases, there were 198 cases of cardiac malformation monitoring, accounting for26%, 61 cases out of 198 cases were diagnosed with BTBS, accounting for 2.8%, Rate of BTBS inchildren who came to ultrasound examination. Postnatal check up is 17%.Conclusions: Examination of cardiac abnormalities on ultrasound from 18 weeks to 28 weeksgestation is very valuable in the attitude of treatment for patients.
Keywords: Congenital defects, Defects.